Contra Snapshot Ockhamism - Widerker, David (International journal for philosophy of religion, 1996)
Given the failure of Fischer's and other entailment accounts of the soft/hard fact distinction, the conclusion that emerges is that the Ockhamist cannot justify his treating the likes of F1 as soft facts about the past by appealing to an entailment account of soft/hard facthood. As we have seen, accounts of this sort are seriously flawed in that they overlook the point that a fact may entail a fact about the future and still be a genuine past fact. Call this problem ‘the entailment problem’. Even if the Ockhamist can evade this problem by adopting a different account of the soft/hard fact distinction, he is still faced with what Fischer has called the problem of ‘hard-core soft facts’,Footnote 1 i.e. the problem that by having power over facts such as F1, the agent also gets power over hard facts about the past. Although Fischer's way of raising the problem is certainly convincing,Footnote 2 the problem can be raised also in another way by means of the following consideration. Note that (unlike regular soft facts) facts regarding God's forebeliefs of human actions can causally contribute to the occurrence of events preceding those actions. For example, we can conceive of a situation in which God, in the light of his belief that Jones will attempt to murder Smith at T5, reveals this fact to Smith at T3 by causing the occurrence of an event E, e.g. Smith's hearing at T3 a voice telling him about what is going to happen. Now, if God's belief that Jones will attempt to kill Smith were, as the Ockhamist maintains, a soft fact about the past over which Jones has power, Jones could by refraining from his attempt to kill Smith, bring about the non-occurrence of E. This would be a violation PFP.Footnote 3 , Both the ‘entailment problem’ and the problem of ‘hard-core soft facts’ pose a serious difficulty for the Ockhamistic approach to the freedom-foreknowledge dilemma. Hence, in the absence of an adequate solution to them, the theological compatibilist would be well-advised to turn to other ways of solving that dilemma.